Evaluation of Value Capture Strategies for Public Private Partnership Projects in Railway System Projects to be Built in Istanbul City. - DÖNMEZ, CEM ÇAĞRI (My University, 2018)
For urban rail lines, there is a need for resources at all stages such as planning, construction and operation. In financing these structures with large budgets and requiring specialized construction, it is possible to implement not only the use of state resources but also many models of Public-Private Partnership (PPP). This method, which can be called alternative financing, will make a significant contribution to the realization of investment auctions and will also contribute to the rapid commissioning / finalization of investments. This model has been tried many times in the world and it has been evaluated that it will be more successful for all the types of the metro (cable car, light subway, monorail, street tram which can be called as a relatively light subway investment. For rail lines when alternative financing is required, it would be appropriate to increase the diversity of income items in feasibility reports. In this context, in addition to travel revenues, real estate value tax, Tax credit financing, goodwill and real estate development partnership can provide income. Real estate prices increase in the area where rail system investment is made and this situation is used as a direct marketing tool by construction companies. On the other hand, in cases where Station structures have to be constructed outside the public area, the cost of expropriation for the project is increasing and financing needs are increasing. For the transportation investment projects carried out as Public-Private Partnership Project (PPP), the use of value increase strategies other than passenger revenues will be beneficial in terms of financing. The demographic and geographic features of the project will be decisive in the determination of the Value Capture Strategies (VCS) to be used. Within the scope of this project; VCS strategies were evaluated in PPP models by using analytical hierarchy process (AHP) with expert opinion in rail system projects to be carried out in Istanbul.

Şehir içi raylı sistem hatları için; planlanma, yapım ve işletme gibi tüm aşamalarda birçok kaynak ihtiyacı bulunmaktadır. Büyük bütçeli ve inşaatı ihtisas gerektiren bu yapıların finansmanında, sadece devlet kaynakları kullanımı değil birçok kamu özel işbirliği modelinin de hayata geçirilmesi mümkün görülmektedir. Alternatif finansman olarak adlandırılabilecek bu yöntem, yatırım ihalelerinin gerçekleştirilmesinde önemli katkı sağlayacağı gibi, yatırımların hızlı bir şekilde hizmete alınması / sonuçlandırılmasında da katkı sağlayacaktır. Bu model dünyada birçok kez denenmiş ve göreceli olarak hafif metro yatırımı olarak isimlendirilebilecek metro türlerinde (teleferik, hafif metro, havaray, cadde tramvayı) daha başarılı olacağı değerlendirilmiştir.Alternatif finansmanı istenen raylı sistem hatları için, fizibilite raporlarında gelir kalemlerinin çeşitliliğin artırılması uygun olacaktır. Bu kapsamda yolculuk gelirlerinin yanında, Gayrimenkul Değer Vergisi, Vergi Artış Yoluyla Finansman (Tax Increment Financing), Şerefiyeler ve Gayrimenkul Geliştirme Ortaklığı gibi yöntemler ile gelir sağlanabilecektir. Özellikle, raylı sistem yatırımları metropol şehirlerde emlak fiyatlarını doğrudan etkilemektedir. Raylı sistem yatırımı yapılan alanlarda gayrimenkul fiyatları artmakta ve bu durum inşaat firmaları tarafından doğrudan bir pazarlama aracı olarak kullanılmaktadır. Diğer taraftan istasyon yapılarının kamu alanı dışında inşa edilmesi zorunluluğu olduğu durumlarda proje için kamulaştırma maliyeti oluşturmakta, finansman ihtiyacı artmaktadır. Kamu-Özel İşbirliği Projesi (PPP) olarak yapılan ulaştırma yatırım projeleri için, yolcu gelirleri dışındaki değer artış stratejilerinin kullanılması finansmanın sağlanması açısından faydalı olacaktır. Kullanılacak Değer Yakalama Stratejileri’nin (VCS) belirlenmesinde ise, projenin demografik ve coğrafi özellikler belirleyici olacaktır. Bu proje kapsamında; İstanbul’da yapılacak raylı sistem projelerinde uzman görüşü ile Analitik Hiyerarşi Süreci (AHP) kullanılarak, PPP modellerinde VCS stratejileri değerlendirilmiştir.
İstanbul Şehrinde İnşa Edilecek Raylı Sistem Projelerinde Kamu Özel İşbirliği Projeleri için Değer Yakalama Stratejilerinin Değerlendirilmesi
Keywords: Kimya, Uygulamalı; Kimya, Tıbbi; Kimya, Organik; Çevre Bilimleri; Matematik; Fizik, Matematik; Mühendislik, Kimya; Mühendislik, Elektrik ve Elektronik; Endüstri Mühendisliği; Mühendislik, Makine; Malzeme Bilimleri, Biyomalzemeler